The use of dandelion root (Taraxacum officinalis Wigg.) for sugar-concentrates - Косоголова, Л. О.; Лошицький, П. П.; Кривутенко, І. С.; Поліщук, Б. В.; Яблонська, К. М. (Problems of Environmental Biotechnology, 2017)
The influence of electromagnetic radiation of different frequencies (50 Hz, 100 kHz, 60 GHz) on the efficiency of extraction of sugars from root dandelion (Traxacum officinale Wigg.). The greatest effect of electromagnetic radiation detected at the 25-minute treatment extracts at a frequency of 60 GHz.